Right Ventricular Dysfunction Predicts Outcome in Acute Heart Failure - Berrill, Max; Ashcroft, Eshan; Fluck, David; John, Isaac; Beeton, Ian; Sharma, Pankaj; Baltabaeva, Aigul (Frontiers in Cardiovascular Medicine, 2022)
Aim The severity of cardiac impairment in acute heart failure (AHF) predicts outcome, but challenges remain to identify prognostically important non-invasive parameters of cardiac function. Left ventricular ejection fraction (LVEF) is relevant, but only in those with reduced LV systolic function. We aimed to assess the standard and advanced parameters of left and right ventricular (RV) function from echocardiography in predicting long-term outcomes in AHF. Methods A total of 418 consecutive AHF patients presenting over 12 months were prospectively recruited and underwent bedside echocardiography within 24 h of recruitment. We retrospectively assessed 8 RV and 5 LV echo parameters of the cardiac systolic function to predict 2-year mortality, using both guideline-directed and study-specific cutoffs, based on the maximum Youden indices via ROC analysis. For the RV, these were the tricuspid annular plane systolic excursion, RV fractional area change, tissue Doppler imaging (TDI) peak tricuspid annular systolic wave velocity, both peak- and end-systolic RV free wall global longitudinal strain (RV GLS) and strain rate (mean RV GLSR), RV ejection fraction (RVEF) derived from a 2D ellipsoid model and the ratio of the TAPSE to systolic pulmonary artery pressure (SPAP). For the LV, these were the LVEF, mitral regurgitant ΔP/Δt (MR dP/dt), the lateral mitral annular TDI peak systolic wave velocity, LV GLS, and the LV GLSR. Results A total of 7/8 parameters of RV systolic function were predictive of 2-year outcome, with study cutoffs like international guidelines. A cutoff of < −1.8 s–1 mean RV GLSR was associated with worse outcome compared to > −1.8 s–1 [HR 2.13 95% CI 1.33–3.40 (p = 0.002)]. TAPSE:SPAP of > 0.027 cm/mmHg (vs. < 0.027 cm/mmHg) predicted worse outcome [HR 2.12 95% CI 1.53–2.92 (p < 0.001)]. A 3-way comparison of 2-year mortality by LVEF from the European Society of Cardiology (ESC) guideline criteria of LVEF > 50, 41–49, and < 40% was not prognostic [38.6% vs. 30.9 vs. 43.9% (p = 0.10)]. Of the 5 parameters of LV systolic function, only an MR dP/dt cutoff of < 570 mmHg was predictive of adverse outcome [HR 1.63 95% CI 1.01–2.62 (p = 0.047)]. Conclusion With cutoffs broadly like the ESC guidelines, we identified RV dysfunction to be associated with adverse prognosis, whereas LVEF could not identify patients at risk.